Influence of porosity on anisotropic thermal conductivity of SiC fiber reinforced SiC matrix composite: A microscopic modeling study. Issue 18 (15th December 2020) - Wang, Jun; Chen, Yunsheng; Feng, Yajie; Zhao, Gang; Jian, Xigao; Huang, Qing; Yang, Lingwei; Xu, Jian
Abstract: The effect of porosity on the effective thermal conductivities calculation for continuous SiC fiber reinforced SiC matrix composites (SiCf /SiC) was studied in this work by finite element modeling. A three-dimensional representative volume element (RVE) containing detailed geometric features (fibers, matrix, fiber coatings and pores) was generated to rebuild the microstructure of SiCf /SiC and used to numerically calculate the effective transversal and longitudinal thermal conductivities of SiCf /SiC. Markworth model and parallel model were chosen as theoretical models to calculate the transversal and longitudinal thermal conductivities respectively. The numerical results obtained by RVE models were validated by comparison with the theoretical and experimental results. The results highlight the existing theoretical models cannot well predict the transversal thermal conductivity of SiCf /SiC with the existence of pores. In the analysis of the effect of porosity, real pore structure in SiCf /SiC was investigated to revel the relationship between porosity and the effective thermal conductivities. In the case of longitudinal thermal conductivity, the parallel model plus the linear term of porosity can still be used to predict the longitudinal thermal conductivity. As for the transversal thermal conductivity, a more proper Markworth model for SiCf /SiC transversal thermal conductivity calculation calibrated by incorporating porosity is proposed to efficiently calculate the transversal thermal conductivity at the end of this paper.